Role of Lactate Transporters in Pulmonary Hypertension - Bermes, Daniel Gerd; Justus Liebig University Giessen (My University, 2022)
Background: In Pulmonary Hypertension (PH), pulmonary vascular cells favor cytosolic glycolysis instead of oxidative phosphorylation, to cover their energy demand. This feature is also known as Warburg effect. The metabolic change is accompanied by a distinct lactate production. Still, the expression and functional relevance of lactate transporters in PH have not yet been investigated. Studies originated from cancer research highlighted the relevance of the lactate transporters, Monocarboxylate Transporter (MCT) 1 and 4, in disease pathobiology. In this study, the role of MCT1 and 4 in the context of PH is addressed. Methods: MCT1 and 4 expression was investigated in lung tissue homogenates derived from IPAH and donor patients. In vitro experiments were performed in human pulmonary arterial smooth muscle cells (hPASMCs). In hPASMCs the expression profile upon hypoxic and non-hypoxic stimuli was investigated. The effect of MCT1 and/or 4 knockdown or pharmaceutical inhibition, using AZD3965 or syrosingopine, on functional characteristics in hPASMCs were investigated. For this purpose, proliferative capacity, cell migration, apoptosis rate, cell viability and extracellular lactate concentration were determined. The potential of MCT1 and 4 as disease biomarkers were evaluated by measuring the circulating concentration in plasma samples, derived from non-PH and PH patients. Results: The mRNA and protein expression of MCT1 and 4 were increased in the lungs of IPAH patients compared to donor lungs. Chronic hypoxia, PDGF and TGFβ stimulation induced MCT4 expression in hPASMCs, whereas MCT1 was not influenced by any of the investigated stimuli. Dual inhibition of MCT1 and 4 by syrosingopine reduced lactate export, induced apoptosis and decreased cell proliferation and migration with absent cytotoxic side-effects, in hypoxic conditions. Circulating MCT1 and 4 did not reveal a diagnostic or prognostic benefit as a disease biomarker. Conclusion: MCT1 and 4 play an important role in PH pathobiology. At least one functional transporter is necessary for disease progression. Dual inhibition of MCT1 and 4 represent a promising therapeutic approach. Circulating MCT1 and 4 are no suitable PH biomarkers.
Keywords: Pulmonary Hypertension; ddc:610